A Genuine Stannylone with a Monoatomic Two‐Coordinate Tin(0) Atom Supported by a Bis(silylene) Ligand. (1st December 2021) - Xu, Jian; Dai, Chenshu; Yao, Shenglai; Zhu, Jun; Driess, Matthias
Abstract: The monoatomic zero‐valent tin complex (stannylone) {[Si II (Xant)Si II ]Sn 0 } 5 stabilized by a bis(silylene)xanthene ligand, [Si II (Xant)Si II =PhC(NtBu)2 Si(Xant)Si(NtBu)2 CPh], and its bis‐tetracarbonyliron complex {[Si II (Xant)Si II ]Sn 0 [Fe(CO)4 ]2 } 4 are reported. The stannylone 5 bearing a two‐coordinate zero‐valent tin atom is synthesized by reduction of the precursor 4 with potassium graphite. Compound 4 results from the Sn II halide precursor {[Si II (Xant)Si II ]Sn II Cl}Cl 2 or {[Si II (Xant)Si II ]SnBr2 } 3 through reductive salt‐metathesis reaction with K2 Fe(CO)4 . According to density functional theory (DFT) calculations, the highest occupied molecular orbital (HOMO) and HOMO‐1 of 5 correspond to a π‐type lone pair with delocalization into both adjacent vacant orbitals of the Si II atoms and a σ‐type lone pair at the Sn 0 center, respectively, indicating genuine stannylone character. Abstract : The bis( N ‐heterocyclic silylene)‐stabilized stannylone with a two‐coordinate Sn 0 atom and its bis‐Fe(CO)4 complex have been synthesized and structurally characterized by NMR spectroscopy and X‐ray crystallography. Their bonding situations have been uncovered by density functional theory calculations, indicating a genuine stannylone character with two lone pairs of electrons at the tin atom.